Student team achievement divisions (STAD) and jigsaw learning in terms of numerical abilities: The effect on students' mathematics learning outcomes - Sa'adiah, Halimatus; Syaiful, Syaiful; Hariyadi, Bambang; Yudistira, Pengki (Desimal: Jurnal Matematika, 2021)
The learning process is inseparable from the strategies and learning models used. The application of the learning model is an effort to improve student's abilities and learning outcomes. This research aims to determine the effect of the STAD and Jigsaw cooperative learning models in terms of numerical abilities on learning outcomes. Data collection was carried out using a test instrument to see students' mathematics learning outcomes. Data analysis is carried out by using a two-way ANOVA statistical test and further testing using the Tukey test. Based on the results of the research, it can be concluded that there is a significant effect between the STAD type cooperative learning model in terms of numerical abilities on mathematics learning outcomes, but for the Jigsaw model there is no effect of the learning model in terms of numerical abilities on mathematics learning outcomes and there is no difference between classes that using the STAD model with a class that uses the JIGSAW model in terms of numerical abilities on students' mathematics learning outcomes.